Strategi Negosiasi Identitas Suku Masserempulu: Analisis Lintas Budaya dalam Konteks Hegemoni Budaya Bugis dan Toraja - Sjarif, Nurfadila; Najamuddin; Alimin Alwi (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2026)
This study analyzes the identity negotiation strategies developed by the Massenrempulu tribe in response to the cultural hegemony of the Bugis and Toraja tribes in South Sulawesi. Using a qualitative ethnographic approach, the study was conducted over nine months in three districts: Enrekang, Tana Toraja, and Bugis. Data were collected through participant observation, in-depth interviews with 32 informants, and focus group discussions. The results of the study reveal five interrelated identity negotiation strategies: (1) Selective Cultural Hybridity, in the form of bricolage practices in language and architecture; (2) Symbolic Resistance, through the affirmation of identity as “To Kaili” and the preservation of core traditional rituals; (3) Culture-Based Creative Economy, by developing niche markets for traditional weaving and cuisine; (4) Digital Cultural Diplomacy, namely the use of social media to build independent narratives; and (5) Contextual Adaptation, which demonstrates the flexibility of identity based on the situation. The findings of this study enrich Berry's theory of acculturation by demonstrating the complexity of the adaptation process in the context of multiple hegemonies. This study also makes an important contribution to the development of multicultural education that is more inclusive, critical, and responsive to the dynamics of local identities.